Bluehoc-based simulation study of user data throughput in Bluetooth-enabled devices. (1st October 2010) - Rahat, Syed; Anpalagan, Alagan
Bluetooth technology aims at allowing short-range communication between portable and/or fixed devices. It uses RF links in unlicensed ISM band. Its key features are low power and cost for data and voice transfer between communication devices and PCs. In this article, a Bluehoc-based simulation study is done to analyse various parameters that affect Bluetooth piconet throughout. It is noted that: 1) user data transfer rate is affected by distance, number of slaves, slave start time and master inquiry timeout; 2) connection stability for SCO and ACL links depends differently on start time and inquiry timeout.